Pengaruh Kualitas Layanan, Citra Perusahaan, Kepuasan Konsumen dan Penanganan Komplain Terhadap Loyalitas Pelanggan J&T Express Singosari - Zahrok’u Syarofah; Rois Arifin; Alfian Budi Primanto (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
Abstrack This study aims to determine the effect of service quality, company image, customer satisfaction and complaint handling. The object of this research is the Singosari community with a sample size of 102 respondents who have made deliveries to J&T Express. The sampling technique used purposive sampling. Data collection techniques using questionnaires and data analysis tools. Based on the results of partial research analysis, service quality has a significant effect on customer loyalty. While partially service quality has a significant effect on customer loyalty. Meanwhile, partially, company image has a significant effect on customer loyalty. While partially customer satisfaction has a significant effect on customer loyalty. Meanwhile, the partial handling of complaints has a significant effect on customer loyalty. Keywords: Effect of Service Quality, Company Image, Customer Satisfaction and Complaint Handling.